Vision-Based Dynamic Displacement Measurement of Isolation Bearing - Yizhe He; Yu Dang (Advances in Civil Engineering)
The existing computer vision-based structural displacement measurement method can only obtain structural displacement when the camera is fixed or the pose of the camera is known at all times. However, the aforementioned conditions cannot be met when an earthquake occurs. Therefore, this study presents a method to achieve a dynamic displacement measure of an isolated bearing from a video without the known camera motion: two cameras are set up along the horizontal orthogonal direction, and circular targets are set at the upper and lower connecting plates of the isolation bearing. A combination of HSV color space, Canny edge detection, and Hough transform circle detection is used to obtain the dynamic displacement of the isolation bearing. This task is done by measuring the relative displacement between the upper and lower target points. A basic mechanical performance test of LRB500 isolation bearing is used to verify the proposed method. The result shows that the horizontal displacement time history of the isolation bearing obtained by this method is almost the same as the result obtained by the displacement meter whether the camera is moving or fixed. However, compared with the results measured by the displacement meter, the absolute error of the peak horizontal and vertical displacements are both less than 1 mm, which indicates that the proposed method can be used in displacement monitoring under long-term load and earthquake action of isolation bearing.